2020
DOI: 10.1108/bfj-10-2019-0785
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward food fraud in Israel and Germany

Abstract: PurposeThe current research focused on attitudes toward food fraud (AFF) and examined the impact of types of food fraud, gender differences, and country of residence.Design/methodology/approachA convenience sample of German (n = 151) and Israeli (n = 496) participants was recruited through an online survey. They filled out a sociodemographic questionnaire and AFF scale, which includes three subscales: organic fraud, kosher fraud, and spraying fraud.FindingsThe results indicate that there is a significant effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…Our study's participants expressed very low support for capital punishment. In general, our findings about Israeli's attitudes toward crimes and criminals are consistent with those in certain Western cultures (Herzog, 2017;Levy & Kerschke-Risch, 2020), but not with the higher support levels that U.S. studies have shown (e.g., 53% support the death penalty reinstatement in Michigan; Adinkrah & Clemens, 2018). Lower capital-punishment support may indicate that Israelis value more the sanctity of life, as expressed by basic notions of Judaism, the country's main religion (Calvert, 2019;Halevy & Halevy, 2018).…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Our study's participants expressed very low support for capital punishment. In general, our findings about Israeli's attitudes toward crimes and criminals are consistent with those in certain Western cultures (Herzog, 2017;Levy & Kerschke-Risch, 2020), but not with the higher support levels that U.S. studies have shown (e.g., 53% support the death penalty reinstatement in Michigan; Adinkrah & Clemens, 2018). Lower capital-punishment support may indicate that Israelis value more the sanctity of life, as expressed by basic notions of Judaism, the country's main religion (Calvert, 2019;Halevy & Halevy, 2018).…”
Section: Discussionsupporting
confidence: 54%
“…Research on attitudes toward capital punishment tends to focus on the American public. However, the similarities between the Israeli public and Western societies in attitudes toward offenders (Herzog, 2017;Levy & Kerschke-Risch, 2020) may reveal insights that are true for the Western world in general. We hypothesized that: H 1 : Crime severity predicts support of capital punishment: Crimes rated as more severe are more likely to be regarded as eligible for capital punishment.…”
Section: Crime Type and Severitymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, there is evidence that religiosity is positively associated with values such as the need to preserve social order and uncertainty avoidance beyond such factors as age, gender, education, and income (Pepper et al, 2010;Schwartz and Huismans, 1995). Considering that in some cases, higher uncertainty avoidance is related to more negative attitudes toward offenders (Levy and Kerschke-Risch, 2020), perhaps the search of religious respondents for certainty and order manifests itself in their tendency to prefer incarceration, which poses a lesser risk to community safety. Future studies should explore the relationship between religiosity, values, and attitudes toward community correction.…”
Section: Individual Factorsmentioning
confidence: 99%
“…Valuable components or attributes i.e., degree of economic differential between food product and substitute-the greater the differential the greater the motivation for fraud Vulnerability is the extent to which an individual, organization, supply chain or national food system is at risk from, or susceptible to, attack, emotional injury or physical harm, or damage from intentional illicit activity [63]. Much has been written about the vulnerability of organic foods to instances of fraud [15], and this can be extended to other credence-based foods such as kosher and halal [64], mediated by the characteristics of individual sectors and the organizations themselves [65]. Product testing protocols are being developed to identify conventional food posing as its organic counterpart but introducing product testing can increase costs and friction in global supply chains and reduce the degree of acceptance of institutional trust mechanisms.…”
Section: Economic Drivers Cultural and Behavioral Driversmentioning
confidence: 99%